Teacher Practical and Pedagogical Skills Acquisition (TPPSA) Framework For Skills Acquisition In Leatherwork: The Case Of Tamale Technical University - Issah, Mohammed Seini; Tachie-Menson, Akosua; Harry Barton, Essel (Papanda Publishier, 2025)
This paper presents a framework for the instruction of Leatherwork and practical programs aimed at skills acquisition. The development of the pedagogical framework was inspired by observations of teaching and learning in Leatherwork, as well as a series of interviews conducted at the Department of Art and Design Innovation at Tamale Technical University. Additionally, the framework draws from various models, including Technological Pedagogical Content Knowledge TPACK developed by Koehler and Mishra (2009), the Successive Approximation Model (SAM) model, and the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model as proposed by Molenda and Pershing (2003), along with the Ghana National Teachers Guide (2017) in conjunction with established teachers' standards. The pedagogical framework is designated TPPSA. The development of the Teacher Practical and Pedagogical Skills Acquisition (TPPSA) framework is essential for the effective teaching of both content and practical knowledge in technical universities. This structured framework is designed to facilitate skills acquisition among technical university students. This paper commences with a brief introduction to leatherwork as a practical program within Ghanaian technical universities, thereby situating the pedagogical framework within the context of leatherwork. Additionally, it addresses the challenges associated with the teaching and learning of practical courses in technical universities, which underscore the necessity for the development of the TPPSA pedagogical framework. The TPPSA framework for skills acquisition is articulated in detail as a complex interaction among three domains of knowledge: teacher philosophy, pedagogical strategies, and practical skills. The interplay of these domains, both theoretically and in practice, engenders the flexible knowledge required to effectively cultivate content knowledge and practical skills among students in technical universities.